Pathways into and out of the Labor Market After Receiving Social Benefits: Cumulative Disadvantage or Life Course Risk?. Issue 4 (2nd October 2018) - Hümbelin, Oliver; Fritschi, Tobias
ABSTRACT: Based on Swiss register data, we conduct a cohort analysis over four years to study the paths that individuals take back into or out of the labor market after receiving benefits. To gain insight into this dynamic from a perspective of social stratification and life course theory, we analyze marginal effects from multinomial logistic regression models. Our study reveals that even in a wealthy country like Switzerland, not everyone is able to get back into the labor market and earn a self-sustaining income. Reintegration is strongly influenced by previously attained status, as measured by income and education. Controlling for income and education, some differences related to gender and citizenship remain. The strongest driver of pathways out of the labor market after claiming benefits, however, relates to life course characteristics.